ORE identifies extreme expression effects enriched for rare variants - Richter, F (Bioinformatics, 2019)
MOTIVATION: Non-coding rare variants (RVs) may contribute to Mendelian disorders but have been challenging to study due to small sample sizes, genetic heterogeneity and uncertainty about relevant non-coding features. Previous studies identified RVs associated with expression outliers, but varying outlier definitions were employed and no comprehensive open-source software was developed. RESULTS: We developed Outlier-RV Enrichment (ORE) to identify biologically-meaningful non-coding RVs. We implemented ORE combining whole-genome sequencing and cardiac RNAseq from congenital heart defect patients from the Pediatric Cardiac Genomics Consortium and deceased adults from Genotype-Tissue Expression. Use of rank-based outliers maximized sensitivity while a most extreme outlier approach maximized specificity. Rarer variants had stronger associations, suggesting they are under negative selective pressure and providing a basis for investigating their contribution to Mendelian disorders. AVAILABILITY AND IMPLEMENTATION: ORE, source code, and documentation are available at https://pypi.python.org/pypi/ore under the MIT license. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.